Laparoscopic and endoscopic cooperative surgery (LECS) to overcome the limitations of endoscopic resection for colorectal tumors - Tamegai, Yoshiro; Fukunaga, Yosuke; Suzuki, Shinsuke; Lim, Dennis N.F.; Chino, Akiko; Saito, Shoichi; Konishi, Tsuyoshi; Akiyoshi, Takashi; Ueno, Masashi; Hiki, Naoki; Muto, Tetsuichiro (Endoscopy International Open, 2018)
Background and study aims We developed a laparoscopy endoscopy cooperative surgery (LECS) to overcome the limitations of endoscopic resection for colorectal tumors. The aim of this study was to evaluate the feasibility of LECS, which combines endoscopic submucosal dissection (ESD) and laparoscopic partial colectomy.Patients and methods We performed LECS for 17 colorectal tumors in 17 patients (male:female 10:7; mean age, 66.5 years). The clinicopathological outcomes of these 17 cases and the feasibility of LECS were evaluated retrospectively. Indications for LECS were as follows: 1) intramucosal cancer and adenoma accompanied by wide and severe fibrosis; 2) intramucosal cancer and adenoma involving the diverticulum or appendix; and 3) submucosal tumors. Results We successfully performed LECS procedures in 17 cases (intramucosal cancer [n = 6], adenoma [n = 9], schwannoma [n = 1], and gastro-intestinal stromal tumour [GIST] [n = 1]. Mean tumor diameter was 22.4 mm (range, 8 – 41 mm). LECS was successfully performed in all 17 cases without conversion to open surgery; the R0 rate was 100 %. LECS was applied to the following situations: involving the appendix (n = 6), tumor accompanied by severe fibrosis (n = 5), involving the diverticulum (n = 3), submucosal tumor (n = 2), and poor endoscopic operability (n = 1). We experienced no adverse events (e. g., leakage or anastomotic stricture) and the median hospital stay was 6.4 dayus (range, 4 to 12). All 17 patients who were followed for ≥ 3 months (median, 30.8 months; range, 3 – 72 months) showed no residual/local recurrence. Conclusion LECS was a safe, feasible, minimally invasive procedure that achieved full-thickness resection of colorectal tumors and showed excellent clinical outcomes.